Hubungan Status Gizi terhadap Premenstrual Syndrome pada Mahasiswi Kesehatan dan Non-Kesehatan Universitas Airlangga - Sofia Zahrani (Antigen : Jurnal Kesehatan Masyarakat dan Ilmu Gizi, 2025)
Premenstrual Syndrome (PMS) is a collection of physical and emotional symptoms occurring prior to menstruation that can disrupt daily activities. Dietary patterns and nutritional status are known to influence PMS symptoms. This study aims to analyze the relationship between dietary intake (energy, carbohydrates, protein, fat, magnesium, and vitamin B6) and nutritional status (based on Body Mass Index/BMI) with the incidence of PMS among female students from both health and non-health study programs at Universitas Airlangga. This research employed an analytical observational study with a cross-sectional design. A total of 103 female students from the 4th semester of the Nutrition and Islamic Economics study programs were selected through proportional random sampling. Data were collected using questionnaires on respondent characteristics, a Semi-Quantitative Food Frequency Questionnaire (SQ-FFQ), anthropometric measurements, and the Shortened Premenstrual Assessment Form (SPAF). Data analysis was performed descriptively and inferentially using Spearman's rank correlation test. The results showed a significant relationship between energy intake (p = 0.002) and fat intake (p = 0.001) with PMS. No significant relationship was found for carbohydrate, protein, magnesium, and vitamin B6 intake (p > 0.05). Additionally, nutritional status based on BMI was significantly associated with PMS (p = 0.001), indicating that both underweight and overweight students were more likely to experience PMS. These findings highlight that imbalanced energy and fat intake, as well as abnormal nutritional status, may be contributing factors to PMS. Therefore, increasing awareness of proper nutrition and reproductive health is essential to reduce PMS symptoms among female students.